"تعليقٌ لطيفٌ على بِسْمِ اللَّـهِ الرَّحْمَـٰنِ الرَّحِيمِ" لشهاب الدين أحمد بن غانِم بن سالم النفراوي المالكي(ت1126ه) -دراسة وتحقيق - - شنوف, عبد اللطيف; سعود, أيمن (University of Eloued-جامعة الوادي, 2022)
"ملخص البحث هذا البحث الذي بين أيدينا هو دراسة ضمن منهج وفن تحقيق التراث، ويهدف إلى إبراز أحد المصنفات العلمية التي لم تر النور بعد، فأردنا أن نحلِّيها بِحِلْيَةِ التحقيق، والتدقيق، والبيان، حتى يخرج للنور على وفق مراد المؤلف ومبتغاه، أو أقرب إلى ذلك. فقد أسْتُهِل هذا التحقيق بمبحث دراسي نظري، تم فيه شرحُ صورة الـمُؤَلَّف والـمؤَلِّف، بيانا لعصره وحياته، ودراسة للمصنف ماهية ومنهجاً. ثم يلي ذلك القسم قسم التحقيق، وهو القسم التطبيقي للبحث، وفيه خلُصنا إلى أن المؤَلف رحمه الله تطرق خلال شرحه للبسملة إلى علوم شتى، مبيّنا رابط كل علمٍ بها، جامعا لما يتعلق بها، مع التركيز الدقيق على نص الكتاب، تفريغا صحيحا، وتوثيقا لآثاره ونقوله، وضبط ما يحتاج إلى ضبطه من مسائل فقهية ونحوها. ثم إلى خاتمة وفيها أهم النتائج والتي أبرزها: أن هذا الكتاب يُعد من المؤلفات ذوات الموضوع الواحد، التي تيسر على طلاب العلم ورواده جمع شتات هذا الموضوع ولطائفه. ثم وفي الأخير أتممنا العمل بتوصيات رأينا أنها أحق لأن يُنظر فيها، وبهذه الصورة خرج العمل، نسأل الله أن يتممه بالقبول.""This study aims to highlight one of the scientific works that has not yet seen the light, which is within the method and art of heritage investigation This investigation begins with a theoretical part , in which the image of the author and the author was explained, a statement of his era and his life, and a study of the work's nature and method. Then follows the investigation or practical part , which is the applied section of the research, and in it we concluded that the author, may ALLAH have mercy on him, touched, during his explanation of the Basmalah, to various sciences, explaining the link of each science to it, collecting what is related to it, with a careful focus on the text of the book, a correct interpretation, and documenting its effects. And we say, and adjust what needs to be controlled from doctrinal issues and the like. Then to a conclusion, which contains the most important results, the most prominent of which is: This book is one of the books on the same subject, which makes it easier for students and pioneers of science to collect the scattered pieces of this topic and its spectrum. In the end, we completed the work with recommendations that we thought were more worthy to be considered, and in this way the work came out. We ask ALLAH to complete it with acceptance. "
مذكرة ماستر
Keywords: التعليق على البسملة، النفراوي، تحقيق مخطوط; Commentary on the Basmala, Al Nafrawi, manuscript investigation